Druglikeness of Flowerophoric Model - Bisht, Kavita; Maithani, Alok; Kush, Luv (Asian Journal of Pharmaceutical Research and Development, 2019)
Angiospermic biodiversity is composed of extraordinary versatile flowers of different shapes, colors and aromas. Recently flowers have emerged as the complementary medicine. The druglikeness of commonly occurring terpenoids, flavonoids and pigments in the flowers was rationalized to suggest flowerophoric model at naturotherapeutical level.